2018
DOI: 10.1016/j.bbmt.2017.12.656
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of HPV Quadrivalent Vaccine in Women after Allogeneic HCT is Comparable to Healthy Volunteers

Abstract: We studied the outcome significance of pre-HCT colonization with intrinsics by reviewing the medical records of all allo-HCT recipients with available pre-HCT rectal swab or stool culture results at our institution (2011)(2012)(2013)(2014)(2015)(2016)(2017). Cases with ≥1 positive pre-HCT result for E. gallinarum or E. casseliflavus and no positive test for VRE were defined as intrinsics. Patients with no positive pre-HCT test for intrinsics or VRE, and with at least 2 negative tests for these, were defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As with other vaccinations post-HCT, the full regimen for vaccination is recommended and includes 3 doses at 0, 2, and 6 months [82]. Preliminary evidence indicates that the immunologic response to vaccination is robust and similar to that of immunocompetent women, but whether it decreases the risk of HPV disease warrants further study [83]. Because HPV incidence is high and HPV disease generally occurs later after HCT, combining vaccinating reproductive-aged women up to age 45 or 50 with periodic cervical cytology/HPV screening may be an effective strategy to reduce HPV-associated intraepithelial neoplasia and malignant disease in this population [82,84,85].…”
Section: Breast and Cervical Cancer Prevention Post-hctmentioning
confidence: 99%
“…As with other vaccinations post-HCT, the full regimen for vaccination is recommended and includes 3 doses at 0, 2, and 6 months [82]. Preliminary evidence indicates that the immunologic response to vaccination is robust and similar to that of immunocompetent women, but whether it decreases the risk of HPV disease warrants further study [83]. Because HPV incidence is high and HPV disease generally occurs later after HCT, combining vaccinating reproductive-aged women up to age 45 or 50 with periodic cervical cytology/HPV screening may be an effective strategy to reduce HPV-associated intraepithelial neoplasia and malignant disease in this population [82,84,85].…”
Section: Breast and Cervical Cancer Prevention Post-hctmentioning
confidence: 99%
“…Nonetheless, these studies do not attribute any adverse effects to the HPV vaccine, nor do they alter the course of the original disease, demonstrating its safety [ 53 , 64 , 65 ]. Results from a recent large study on women posttransplant on low dose IST or not on any IST showed that they can mount a response to HPV vaccine and, thus, vaccination will likely become a recommended strategy in the future [ 66 ].…”
Section: Role Of Hpv Vaccinationsmentioning
confidence: 99%